Pengaruh Kompetensi, Motivasi, dan Disiplin Kerja terhadap Kinerja Karyawan Bank BPR Jawa Timur (Cabang Pasuruan) - Werda, Putri Amadah Ayu; Prabowo, Budi (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to investigate the effect of work competence, work discipline, and work motivation on employee performance at the Pasuruan branch of the East Java BPR Bank. Globalization has driven a high level of competition in the world of work, and effective human resource management is becoming increasingly important for organizational success. The performance of individuals in the organization also affects the overall performance of the organization. This study uses a causal research method with a quantitative approach. Data were collected from all employees of the Pasuruan branch of the East Java BPR Bank using a questionnaire with a five-point Likert scale. The results of data analysis show that work competence, work discipline, and work motivation have a positive and significant influence on employee performance. These results are supported by significant statistical values, with a significance level of less than 0.05. The results of the t statistical test show that the three independent variables have a significant positive effect on employee performance. The F test results also show that the regression model as a whole is significant in explaining the variability of employee performance. Thus, it is concluded that work competence, work discipline, and work motivation play an important role in improving employee performance at Bank BPR East Java Pasuruan branch. These results can serve as a foundation for organizational management to develop strategies and policies that support competency development, improved work discipline, and employee motivation. For future research, other factors that have the potential to influence employee performance can be explored. Keywords: Human resource management; Employee performance; Work competency; Work discipline; Work motivation